2011
DOI: 10.1097/meg.0b013e328348a56a
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors therapy and risk of hip fracture

Abstract: These results indicate that PPIs therapy might have the potential risk of hip fracture. Different effects on hip fracture in the subgroup analysis do not support a causal relationship between PPIs and hip fracture. Whether the risk exists warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 34 publications
(60 reference statements)
2
31
0
4
Order By: Relevance
“…Second, the relationship between different classes of possible comparator drug classes and fractures is complex and no clear class of agents could be identified that would serve as an ideal analogue of a placebo controlled randomised trial to treat VMS. H2A/PPIs were selected as the comparator agent because studies have shown that H2As have a trivial or no association with risk of fractures,30–32 while PPIs are associated with a slightly increased risk of fractures 30 33 34. These considerations would tend to drive the differences in fracture risks between the SSRI and our comparator cohort towards the null, provided SSRIs elevate fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the relationship between different classes of possible comparator drug classes and fractures is complex and no clear class of agents could be identified that would serve as an ideal analogue of a placebo controlled randomised trial to treat VMS. H2A/PPIs were selected as the comparator agent because studies have shown that H2As have a trivial or no association with risk of fractures,30–32 while PPIs are associated with a slightly increased risk of fractures 30 33 34. These considerations would tend to drive the differences in fracture risks between the SSRI and our comparator cohort towards the null, provided SSRIs elevate fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies have been limited by significant heterogeneity, and when studies were adjusted to take into account other risk factors for fracture, the use of PPI was not considered to be the cause. Histamine receptor antagonists do not appear to be associated with the risk of fractures [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Second, function of osteoclasts may be inhibited by PPIs, decreasing bone resorption and influencing bone remodelling. These notions are the base for the concerns that PPIs impair bone health, increasing bone fractures, particularly in those with high-dose therapy and/or long-term treatment 42. It is important to note that most studies have been performed in adult patients with risk factors for osteoporosis and bone fractures, and that results are not consistent.…”
Section: Toxicity Profiles Of Ppi In Childrenmentioning
confidence: 99%